KOMODIFIKASI MOMEN NOSTALGIA MUSIK KOES PLUS OLEH GRUP BAND PELITA HATI ASAL KARANGANYAR - Setiawan, Nuri; Setiaji, Denis (Universitas Gadjah Mada, 2024)
This research examines the Koes Plus music performance and the commodification of nostalgic moments by the Pelita Hati group to explain how the Pelita Hati group utilizes a memory or nostalgic moment of Koes Plus song lovers to become a commodity as a process of transforming use value into exchange value. The researcher explains three problem formulations presented in this scientific thesis, namely: (1) What is the general picture of the pop music industry during the Koes Plus era? (2) What is the performance process carried out by Pelita Hati? (3) What is the process of commodification of nostalgic moments that occurs in the Pelita Hati group? In order to explore and understand the phenomenon of music in the context of performances of nostalgic moments through the song Koes Plus, this research uses Vincent Mosco's theory of audience commodification. This research uses a qualitative method described descriptively, in collecting data using the results of observation, interviews, documentation, literature study.The results of this research are that there is a commodification process that occurs in the band Pelita Hati which takes advantage of a memory or nostalgic moment of Koes Plus song fans to gain profit. Apart from that, the Pelita Hati group also brought back songs from Koes Plus with their creativity. From these two things, Pelita Hati tries to reproduce industrial products that it tries to resell. In this case, it can be interpreted that the profits are not only obtained by the Pelita Hati group itself, but also by listeners and audiences who love Koes Plus music. Keywords: Commodification, Nostalgia, Koes Plus